Complex belonging, local concern, voice, and agency: Finnish minority ethnic youths’ construction of civic identity - Kimanen, Anuleena; Khalili, Samaneh; Seger, Aleksi; Alisaari, Jenni (Sage, 2026)
This article develops the concept of civic identity and discusses the implications of a fourfold notion of civic identity and the position of ethnically minoritised youths in civic education. We interviewed 28 ethnically minoritised youths aged 15–19 in Finland and conducted a discursive analysis to determine the kinds of civic identities they had constructed in terms of belonging, concern, voice and agency, and how their minoritised positions played out in them. Constructing local belonging, concern, voice, and agency dominated their discourses in the interviews. Their relationships to ‘Finnishness’ were uneasy. Constructing local belonging helped them avoid this uneasiness but possibly led to their non-construction of concern, voice or agency for broader issues. Understanding civic identity as consisting of belonging, concern, voice, and agency informs civic education regarding how to foster civic identity for all students on different dimensions.